P844 Mucosa associated candida in ulcerative colitis: prevalence and relationship to disease severity. (25th January 2019) - Shah, J; Dutta, U; Rudramurthy, S; Chakrabarti, A; Sharma, P; Popli, P; Srinivasan, R; Das, A; Sinha, S K; Sharma, V; Dhaka, N; Madhavdhare, H; et al.
Abstract: Background: Role of fungal dysbiosis in pathogenesis and severity of ulcerative colitis (UC) is not known. We planned to determine the relationship of presence, nature and quantify Mucosa Associated Candida (MAC) with the disease severity in patients with UC. We planned to determine the relationship of presence, nature and quantify Mucosa Associated Candida (MAC) with the disease severity in patients with UC. Methods: In a prospective study of UC ( n = 96) and non-UC controls ( n = 20), clinical, endoscopic, histological and serological assessment was performed for disease severity. MAC was considered to be present if mucosal biopsy culture grew Candida. Mucosal brush cytology and brush culture was also performed. Candida species identification was done by MALDI. Serum β-D-Glucan was measured by Fungitell assay. Seven UC patients with evidence of Candida were treated with oral Fluconazole and re-evaluated after 14 days. Data are analysed using SPSS and p < 0.05 was considered to be significant. Results: Cases and controls were similar in age and gender. Cases more often had MAC: biopsy culture [33% vs. 5%; p = 0.011], brush cytology [30% vs. 5%; p = 0.019]; brush culture [36.5% vs. 10%; p = 0.021]. Cases had higher colony counts (≥103 CFU/ml) compared with controls: [36% vs. 5%; p = 0.007]. Cases had higher non- C. albicans species compared with controls (25% vs. 0%; p = 0.029). Median β-d -glucan values were higher in cases compared with controls (103.2 pg/ml vs. 66.5 pg/ml; p = 0.011). Cases with MAC had higher median UCDAI, CRP, faecal calprotectin and histological activity compared with those without MAC. Patients with severe disease more often had confluent growth of Candida when compared with patients with moderate or mild disease (50% vs. 7.4% vs. 3%; p = 0.009). Post-therapy all patients( n = 7) showed significant reduction in UCDAI score ( p = 0.017), histological score and faecal calprotectin values. Conclusions: Patients with UC more often have evidence of MAC, higher Candida colony count, higher non- C. albicans species and increased β-d -glucan levels when compared with controls. Disease severity is associated with the presence of MAC and higher β-d -glucan levels.